2018
DOI: 10.20944/preprints201802.0101.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spleen, as an Optimal Site for Islet Transplantation and a Source of Mesenchymal Stem Cells

Abstract: In this review, we show the unique potential of spleen as an optimal site for islet transplantation and a source of mesenchymal stem cells. Islet transplantation is a cellular replacement therapy to treat severe diabetes mellitus, but its clinical outcome is unsatisfactory at present. One factor in clinical success of this therapy is selection of the most appropriate transplantation site. The spleen has been studied for a long time as a candidate site for islet transplantation. Its advantages include physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 106 publications
(133 reference statements)
0
10
0
Order By: Relevance
“…Studies testing effect of thymectomy on transplantation tolerance confirmed the significance of thymus in tolerance induction mechanisms (Vagefi et al 2004 ) and correlation of the BMC engraftment and thymic chimerism with central tolerance induction (Horner et al 2006 ). Spleen, the secondary lymphoid organ, has been also associated with immunomodulation contributing to alloantigen tolerance induction by harboring the myeloid derived suppressor cells (Wang et al 2013 ) and MSC (Krampera et al 2007 ; Sakata et al 2018 ), as well as creating permissive environment to induce regulatory cells, such as Treg (Getts et al 2011 ; Masli et al 2002 ). These studies confirming immunomodulatory role of thymus and spleen support our findings of long-term chimerism maintenance which correlated with the presence of DRCC in spleen and thymus confirmed by immunofluorescence imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Studies testing effect of thymectomy on transplantation tolerance confirmed the significance of thymus in tolerance induction mechanisms (Vagefi et al 2004 ) and correlation of the BMC engraftment and thymic chimerism with central tolerance induction (Horner et al 2006 ). Spleen, the secondary lymphoid organ, has been also associated with immunomodulation contributing to alloantigen tolerance induction by harboring the myeloid derived suppressor cells (Wang et al 2013 ) and MSC (Krampera et al 2007 ; Sakata et al 2018 ), as well as creating permissive environment to induce regulatory cells, such as Treg (Getts et al 2011 ; Masli et al 2002 ). These studies confirming immunomodulatory role of thymus and spleen support our findings of long-term chimerism maintenance which correlated with the presence of DRCC in spleen and thymus confirmed by immunofluorescence imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have even shown that the spleen is another source of this same type of mesenchymal stem cell. 6 In our case, the hypothetical localisation of endometrial stem cells in the spleen is a very promising clue to explain the appearance of endometriosis in splenic parenchyma.…”
Section: Case Descriptionmentioning
confidence: 63%
“…Finally, clinical progress in renal subcapsular transplantation has lagged behind other techniques because of the inelastic and tight nature of the human renal sub-capsular space. 44 Additional strategies to engineer functional kidneys include repopulating synthetic/decellularized scaffolds with kidney-specific cells and transplanting these constructs orthotopically. 45 Unfortunately, these approaches have often failed to recapitulate native kidney functions because of inadequate blood supply.…”
Section: Discussionmentioning
confidence: 99%